Analisa Dan Perancangan Sistem Informasi Penjualan Dan Pengelolaan Persediaan Pada PT Alfajores Bali Enak Menggunakan Metode Waterfall - Ni Putu Nadia Kartika Dewi; Eddy Muntina Dharma; A.A. Istri Ita Paramitha (Smart Techno (Smart Technology, Informatics and Technopreneurship), 2023)
PT Alfajores Bali Enak is a shop that sells cakes, cookies, and various other chocolate preparations. Currently, the recording of sales and inventories by PT Alfajores Bali Enak is still done manually. This causes errors in recording sales and inventory, which makes reports inaccurate. With the analysis and design of this information, the system is expected to assist in recording sales transactions and inventory management. This study uses the waterfall method, starting with needs analysis, planning, modeling, and maintenance. The results of this study are in the form of DFD, ERD, Database, and User Interface designs as an overview of the system to be designed. The method of this information system can later assist users in the process of recording transactions so that they become more accurate. This research only reached the design stage, where it is expected to reach the implementation stage in the future.